If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 * 3) + -1(7 * 2) = y(3 + -2) Multiply 7 * 3 (21) + -1(7 * 2) = y(3 + -2) 21 + -1(7 * 2) = y(3 + -2) Multiply 7 * 2 21 + -1(14) = y(3 + -2) Multiply -1 * 14 21 + -14 = y(3 + -2) Combine like terms: 21 + -14 = 7 7 = y(3 + -2) Combine like terms: 3 + -2 = 1 7 = y(1) Reorder the terms for easier multiplication: 7 = 1y Solving 7 = 1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 7 + -1y = 1y + -1y Combine like terms: 1y + -1y = 0 7 + -1y = 0 Add '-7' to each side of the equation. 7 + -7 + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 0 + -7 -1y = 0 + -7 Combine like terms: 0 + -7 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7
| 3b(3b-27)=0 | | y=9-f(-x) | | 0.35*7= | | 8x/9=-16 | | .2(X+1)+.5x=-0.3(X-4) | | 20+(3y+1)+20+(3y+1)= | | y=7*6+2 | | 2x-3y+14=0 | | 5n+4=14-6 | | 4x+23=10x-19 | | y=ln(sqrt(x^2+-1)) | | 3x4/5x1/8 | | 2m+5n=2 | | 10x+5=25-5 | | 2x^2+4=2x+6 | | 2x-3=5+3x | | (5/6)=((w-2)/4) | | m-10n=6 | | 5(x-2)=16 | | 1=x+0.56x | | 37=5w-13 | | p(x)=2x^2+5x+1 | | 3x^2+26x=16 | | 5x+43=8x-19 | | 12z+28-7z-3= | | 6x+1=34-5x | | 32+(x-2)+32+(x-2)= | | 1.95y+6.834=7.65y-19.8591 | | 70=-7 | | 3*(x-31)=x-13 | | 5-4(6-3)= | | 13x-32=9x-4 |